Caracterización de parásitos gastrointestinales, en la fundación “Esperanza de vida animal” sede norte del municipio de Popayán diagnosticados en el laboratorio de VETELAB (2022)
The main objective of this research was to characterize the gastrointestinal parasites that most frequently affect the canine population of the "Esperanza de vida animal" foundation. The interest in developing this work focused on the implications that gastrointestinal parasites have, not only on animal welfare, but also on public health. This interest allowed veterinary practice to identify the eggs or oocysts of the main gastrointestinal parasites that affect the 40 randomly chosen canines. In this sense, it was possible to establish, through the Willis Flotation Technique, that of the 120 samples, 100% were positive cases for eggs of different parasites. Eggs of 6 species of parasites could be identified. From the nematode phylum, Ancylostoma spp and Toxocara spp were observed, protozoa such as: Entamoeba spp, Cystoisospora spp and Giardia spp and Cestodes such as: Dipylidium spp. It was determined that the eggs of the gastrointestinal parasite of the nematode class that appeared with the highest was Ancylostoma spp with 31.9%, while the least frequent genus was Dipylidium spp with 0.6%. Finding that 100% of the samples were positive for eggs of some parasitic species, it was determined that there are parasites of zoonotic and public health importance in the Foundation. It was established that there is no correlation between sex and the presence of parasites, since gastrointestinal parasites have no predisposition for the gender of canines. In the case of the association between age and the presence of gastrointestinal parasite eggs, it was possible to establish that there is a relationship, since they were observed more in adults and in puppies than in senile ones.